Pengaruh Latihan Passing Bervariasi terhadap Kemampuan Passing Pada Tim Sepak Bola Scorpion Masbagik - Tiassari Janjang Suminar; Lukman (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2025)
This study aims to analyze the effect of varied passing training on improving the passing ability of players from the Scorpion Masbagik football team in 2024. The research employed an experimental method with a one-group pretest-posttest design, without a control group. A total of 20 players participated in the training program over a period of six weeks, with sessions conducted three times per week. Data were collected using passing skill tests administered before and after the treatment. Statistical analysis using a t-test revealed that the t value obtained was 6.49, which exceeded the t table value of 3.08 at a 5% significance level (df = 19). This indicates a significant difference between the pretest and posttest scores, suggesting that varied passing training had a positive effect on players’ passing abilities. The study recommends the use of this training model as an effective strategy for developing basic football techniques, particularly in enhancing passing skills.